Efect of bottom ash fineness on properties of red mud geopolymer - Mandal A.K.; Sinha O.P. (My University, 2025)
Red mud from primary aluminium extraction plants creates environmental pollution due to improper method adaptation in larger scale utilization. The aim of the present investigation was to utilize these wastes for making geopolymer sample with the help of bottom ash to replace sand and also to examine the strength development with the addition of gypsum. Bricks were made with different finenesses of bottom ash and cured in water. Variation in strength, water absorption, and bulk density was determined by variation of red mud-bottom ash ratio, fineness of bottom ash and curing time. Results showed increased strength properties with increasing bottom ash, curing time and fineness up to 30% bottom ash. More red mud content decreased the available silica and alumina content, needed for the polymerization reaction, resulting in a reduction in bricks' strength. The maximum compressive strength 7.56MPa was achieved at 28 days of curing at red mud-bottom ash ratio of 55:30 for fine bottom ash bricks. Obtained results were correlated with the results of previous work and it was concluded that red mud could be polymerized to quite a larger amount with the addition of bottom ash, gypsum for getting comparable properties with those of the commercial materials.